A Systematic Review of the Artificial Intelligence Implications in Shaping the Future of Higher Education - Stefan Popenici; Horațiu Catalano; Gabriela Mestic; Anca Ani-Rus (Babes-Bolyai University, 2023)
Based on a methodological framework structured on quantitative and qualitative analysis methods pursuing a systematic literature review and literature collection design, following the steps proposed by Pickering and Byrne (2014), this study is focused on the analysis of imagined futures of higher education in the age of artificial intelligence (AI). Our study aims to answer the following research questions: (1) What is the imagined future of higher education in the age of artificial intelligence? (2) What are the factors influencing the connection between higher education teaching process and artificial intelligence? (3)What are the effects of students and teachers improving databases and developing ChatGPT? The authors explore the impact of AI in the context of current governance arrangements and ethos of universities in the Western world. The in-depth analysis is aligned with some identified major challenges, opportunities and risks associated with the emergence of artificial intelligence systems, such as technological surveillance or the general access to AI and Large language Models such as ChatGPT in academia and constructs the argument for an informed selection and use of artificial intelligence solutions for learning and teaching in higher education. The analytical framework adopted for this research study is also used to summarise new directions for research in this field to restore the agency of universities, for quality enhancement of higher learning for students, academics and the common good.